2016
DOI: 10.1177/0967828x16659571
|View full text |Cite
|
Sign up to set email alerts
|

Understanding family politics

Abstract: The rise to power of political dynasties in regional Indonesia has been the subject of much critical analysis by scholars and journalists, with most seeing the phenomenon as a symptom of the wider democratic shortcomings of the post-Suharto period. This article examines the successes and travails of political dynasties in regional Indonesia by focusing on the province of Central Kalimantan. It begins by defining political dynasty, differentiating it from allied terms, outlining competing scholarly explanations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
0
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(2 citation statements)
references
References 10 publications
1
0
0
1
Order By: Relevance
“…As shown in Tabel 1, the three research locations showed similar findings in terms of sources of power which became the superiority of incumbents, namely the closeness to the previous ruling figure, which turned out to still have a kinship relationship. This confirms that dynastic and kinship relations are an important source in shaping the superiority of incumbents (Aspinall & As'ad, 2016;Feinstein, 2010;Fiva & Smith, 2018). This relationship becomes the initial capital for incumbents to enter the political arena and enlarge its superiority by controlling economic resources.…”
Section: Bekasi Regencysupporting
confidence: 64%
“…As shown in Tabel 1, the three research locations showed similar findings in terms of sources of power which became the superiority of incumbents, namely the closeness to the previous ruling figure, which turned out to still have a kinship relationship. This confirms that dynastic and kinship relations are an important source in shaping the superiority of incumbents (Aspinall & As'ad, 2016;Feinstein, 2010;Fiva & Smith, 2018). This relationship becomes the initial capital for incumbents to enter the political arena and enlarge its superiority by controlling economic resources.…”
Section: Bekasi Regencysupporting
confidence: 64%
“…Di satu sisi, Pilkada diapresiasi sebagai salah satu mekanisme positif dalam konteks penguatan demokrasi lokal (Sulistiyanto and Erb, 2009, p. 3;Hanif and Pratikno, 2012, p. 89). Namun, di sisi lain, pelaksanaannya masih diwarnai oleh berbagai permasalahan sebagaimana dikritisi banyak kalangan (Choi, 2007;Mboi, 2009;Aspinall and As'ad, 2016) .…”
Section: Pendahuluanunclassified